THE ANALYSIS OF PROPORTIONAL REASONING PROBLEM IN THE INDONESIAN MATHEMATICS TEXTBOOK FOR THE JUNIOR HIGH SCHOOL - Johar, Rahmah; Yusniarti, Sri; Saminan, Saminan (Journal on Mathematics Education, 2018)
The lack of Indonesian students achievement in the international assessment is due to several factors. Students are not familiar with the problems requiring reasoning, in particular the proportional reasoning. This research aims to identify the distribution and the Level of Cognitive Demands (LCD) of the proportional reasoning problems found in the Year 7 and Year 8 mathematics textbooks based on the 2013 curriculum (revised edition 2014). The data collection was conducted by identifying the proportional reasoning problems found in the whole chapters of the textbooks which are then analysed and classified using the Smiths and Stein’s criteria of LCD (1998). The results reveal that the proportional reasoning problems were only found in the three of 17 chapters namely ratio and proportion, rectangle and triangle, and Pythagorean Theorem, which represent different LCD including Lower-LCD (Low-M and Low-P) and Higher-LCD (High-P). Out of 69 proportional reasoning problem found in the textbooks, the percentage of higher-LCD problems (n=29 ; 42.03%) is less than lower-LCD (n=40;57.97%). In addition, the higher-LCD problems found were only the high-P type. None was found to meet the requirement of High-DM demanding students to conduct ‘doing mathematics’, complex approach and self-monitoring or self regulation of students’ cognitive process. It is recommended that the proportional reasoning problems, including some High-DM problems, should be provided in each topic in Indonesian mathematics textbooks.DOI: http://dx.doi.org/10.22342/jme.9.1.4145.55-68